Special Topics in Structural Dynamics, Volume 5 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Dervilis, Nikolaos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Special Topics in Structural Dynamics, Volume 5: Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the fifth volume of nine from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Experimental Methods Analytical Methods General Dynamics & Modal Analysis General Dynamics & System Identification Damage Detection.
Chap 1. Harmonic Forcing of a Two-Segment Timoshenko Beam -- Chap 2. Fastener Fatigue Analysis Using Time Domain Methods for Multiaxial Random Vibration -- Chap 3. Multi-Input Multi-Output Active Vibration Control for High Frequency Random Vibration -- Chap 4. A Method for Cancelling Force Transducer Mass and Inertia Effects -- Chap 5. Efficient Estimation of Clamped Step-thickness Plates FRFs in Industrial Systems -- Chap 6. Modeling, Experimental Verification and Optimization of Seat Structure per ECE R14 -- Chap 7. ODS & Modal Testing Using a Transmissibility Chain -- Chap 8. Correlating Spectral Measurements -- Chap 9. A Differential Evolution Markov Chain Monte Carlo Algorithm for Bayesian Model Updating -- Chap 10. Skin Performance in the Rollover Crashworthiness Analysis of a Cutaway Bus -- Chap 11. Across the Picket Fence - Influence of Sampling Frequency in Automatic Impact Modal Testing -- Chap 12. Estimation of Railway Track Longitudinal Profile using Vehicle-based Inertial Measurements -- Chap 13. Experimental Modal Analysis of Structures with Conventional vs. Contact-free Suspension -- Chap 14. Active Learning Approaches to Structural Health Monitoring -- Chap 15. Multimodal Damping of a Nonlinear Structure with a Passive Piezoelectric Network -- Chap 16. Probability Distribution of von Mises Stress in the Presence of Pre-Load -- Chap 17. Damage Detection Integrating ISHM and LWSHM Techniques -- Chap 18. Structural Health Monitoring of Additively Manufactured Parts Using Fiber Bragg Gratings -- Chap 19. Multi-point Control for Single-Axis Vibration Testing -- Chap 20. Driving a Motion Platform with a Vibration Control Software for Multi-Axis Environmental Testing: Challenges and Solutions -- Chap 21. The Yellow Frame - Experimental Studies and Remote Monitoring of the Structural Health Monitoring Benchmark Structure -- Chap 22. Developing a Passive Vibration Absorber to Generate Traveling Waves in a Beam -- Chap 23. Experimental Assessment of the Effect of Different Tires onComfort of Construction Truck Operators -- Chap 24. Tool Wear Inspection of Polycrystalline Cubic Boron Nitride Inserts -- Chap 25. A New Approach to Dynamic Analysis of a Multi-Span Beam Structure with Multiple Moving Oscillators.
Keywords: Mechanics, Applied; Solids; Multibody systems; Vibration; Mechanical engineering; Civil engineering; Solid Mechanics; Multibody Systems and Mechanical Vibrations; Mechanical Engineering; Civil Engineering